Discrimination and Psychosocial Well-Being of Migrants in Spain: The Moderating Role of Sense of Community - García-Cid, Alba; Gómez-Jacinto, Luis; Hombrados-Mendieta, Isabel; Millán-Franco, Mario; Moscato, Gianluigi (Frontiers in Psychology, 2020)
The discrimination migrants perceive during their adaptation process is one of the main sources of stress and it affects their well-being, health and integration severely. The present study analyses how the sense of community (SOC) can have a protective effect against the perception of discrimination and its negative consequences by verifying the following theoretical model: discrimination predicts three indicators of psychosocial well-being (psychological distress, satisfaction with life and feelings of social exclusion). Furthermore, the theoretical model proposed also considers the hypothesis that SOC has a moderating role on the effect of perceived discrimination regarding the three variables mentioned above. 1714 migrants from Eastern Europe, Africa and Latin America who live in Málaga, Spain, participated in the study. Data were collected using random-route sampling and survey methodology. After carrying out multiple regression analyses, using the PROCESS tool in SPSS 20, the theoretical model was verified: SOC reduces the negative effects of perceived discrimination for the variables psychological distress, satisfaction with life and social exclusion feelings. Therefore, migrants who have a greater SOC experience fewer negative consequences, as compared to those with a lower SOC, for whom the consequences of such variables are more negative. These results highlight the importance for migrants to rebuild social networks in the host country and develop a good SOC. Results also allow the development of intervention patterns to favor positive interactions between native population and migrants.